Lama Bertani dan Hubungannya dengan Cholinesterase Darah Petani Hortikultura di Kecamatan Simpang Empat, Kabupaten Karo - Desta Aulia; Sri Fajar Ayu; Fazidah Agulina Siregar (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Gajah Village is a horticultura supplier area which is occupied by farmers who use pesticide in their farming activities. The use of pesticide by farmers is important to be analyzed, because of the health risks due to the accumulation of pesticide that absorbed by the farmers’ body. This study was aimed to analyze the relationship between the years in farming with the level of cholin-esterase in blood among horticultural farmers in Simpang Empat District of Karo Regency in 2017. The method used in this research was Spearman's rho analysis. The number of sample was 75 farmers that show significant correlation in medium level between the years in farming with blood cholinesterase level. The correlation of those two variables has negative direction. It is advised that the cholinesterase examination could be conducted periodically by the community health centers, so that the farmers can monitor the toxic inside their bodies and can anticipate for the occurrence of higher poisoning.